Re:Poola. Polsko-estońska szkoła języka polskiego i kultury polskiej (Uniwersytet Warszawski – Uniwersytet Talliński) [Re:Poola. The Polish-Estonian School of Polish (Univesity of Warsaw / Tallinn University)] - Małachowicz, Marta; Piotrowska, Joanna (Slavica Revalensia, 2024)
In their review Marta Małachowicz and Joanna Piotrowska survey a newly established educational project first realized in the spring of 2024 and financed by the Polish National Agency for Academic Exchange (NAWA): Re:Poola. Polsko-estońska szkoła języka polskiego i kultury polskiej (Uniwersytet Warszawski – Uniwersytet Talliński). KEYWORDS: Polish Language and Culture, University of Warsaw, Tallinn University, NAWA, L2 Acquisition.